L-Carnitine Mitigates Oxidative Stress and Disorganization of Cytoskeleton Intermediate Filaments in Cisplatin-Induced Hepato-Renal Toxicity in Rats - Elkomy, Ashraf; Abdelhiee, Ehab Yahya; Fadl, Sabreen Ezzat; Emam, Mahmoud Abdelghaffar; Gad, Fatma Abdel-Monem; Sallam, Adham; Alarifi, Saud; Abdel-Daim, Mohamed M.; Aboubakr, Mohamed (Frontiers in Pharmacology, 2020)
Cisplatin (CP) is one of the most active medications in cancer treatment and has some adverse effects such as hepatotoxicity and nephrotoxicity. The present research was planned to determine the protective effects of L-carnitine (LC) against cisplatin (CP)-induced hepato-renal oxidative stress in rats, via investigating of some serum biochemical and tissue oxidative/antioxidant parameters, histological alterations, and immunohistochemical expressions of two different intermediate filaments (IFs) proteins; vimentin (VIM) and cytokeratin 18 (CK18). Twenty-eight rats were divided into four groups (7 rats each). Groups I and II were orally administered saline and LC (100 mg/kg body weight), respectively, once daily for 30 consecutive days. Group III received saline orally once daily and a single dose of CP on the 27th day of the experiment (7.5 mg/kg, intraperitoneal (IP)). Group IV received both LC and CP. Injection of CP significantly (P ≤ 0.05) increased serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) activities and creatinine and urea levels, while serum total protein, albumin, and globulin concentrations significantly (P ≤ 0.05) decreased. In addition, CP induced a dramatic increase in the Malondialdehyde (MDA) level along with a substantial decrease in reduced glutathione (GSH) and catalase (CAT) in the hepato-renal tissues. Histologically, both liver and kidney of the CP treated group revealed marked degenerative changes. Moreover, overexpression of both VIM and CK18 in hepato-renal tissues were noted after CP injection. On the other hand, the administration of LC in the CP injected group (Group IV) restored the biochemical parameters, histological, and immunohistochemical pictures toward the normalcy. In conclusion, LC may be supplemented for chemotherapy with CP to ameliorate its oxidative stress and restore the normal organization of Ifs, especially VIM and CK18 within the CP intoxicated hepato-renal cells.